Value of the Pharmacist in the Medication Reconciliation Process - Splawski, Jennifer (P T, 2016)
Involving pharmacists in the process of comparing the medications that should be ordered for a patient with the new medications that are currently ordered and resolving differences improves accuracy, decreases mortality, and improves transitions of care.